A Biographical Dictionary of Women's Movements and Feminisms : Central, Eastern, and South Eastern Europe, 19th and 20th Centuries - Loutfi, Anna; Daskalova, Krasimira; Haan, Francisca de, 1957- (Book collections on Project MUSE., 2006)
Annotation Contains 150 expertly-researched biographical portraits (with pictures) of women and men who were active in, or part of, women's movements and feminisms in 22 countries in Central, Eastern and South Eastern Europe in the 19th and 20th centuries. The portraits include Romanian princesses, Serbian philosophers and peasants, Latvian and Slovakian novelists, Albanian teachers, Hungarian Catholic social workers, Austrian factory workers, Bulgarian feminist scientists and socialist feminists, Russian radicals and philanthropists, Turkish republican leftist political activists and nationalists, internationally recognized Greek feminist leaders, and so on, from all walks of life. Their stories together constitute a rich tapestry of feminist activity, rejecting the notion that either there was no feminism here, or that it was 'imported from the West.' The editors conclude that "if our biographical subjects were able to bridge the contradictions between feminism, nationalism, socialism, communism, philanthropy and revolution in their own lives--then surely historiansmust adopt similarly open approaches to their own research and methodologies, rather than creating forms of closure through the use of predefined and potentially limited categories."